Synthesis of a smart conductive block copolymer responsive to heat and near infrared light - Bongiovanni Abel, Silvestre Manuel (2019)
A method for the synthesis of a linear block copolymer (PNIPAM-b-PANI), containing a thermoresponsive block (poly(N-isopropylacrylamide), PNIPAM) and a Near Infrared (NIR) light-absorbing block (polyaniline, PANI), is reported. The synthetic approach involves a two-step successive polymerization reaction. First, the radical polymerization of NIPAM is done using 4-aminothiophenol as a chain transfer agent for the obtention of thermosensitive block terminated with an aniline (ANI) moiety. Second, the oxidative polymerization of ANI is initiated in ANI moiety of thermosensitive block to grow the second conductive PANI block. 1H nuclear magnetic resonance (NMR) and FT-IR spectroscopy shows the characteristics peaks of both polymeric blocks revealing the successful copolymerization process. Static Light Scattering (SLS) and UV-Visible combined measurements allowed the determination of the Mw for PNIPAM-b-PANI macromolecule: 5.5 × 105 g mol−1. The resulting copolymer is soluble in water (8.3 g L−1) and in non-aqueous solvents, such as ethanol, formic acid, acetonitrile, and others. Both polymer blocks chains show the properties of the polymer chains. The block copolymer shows a lower critical solution temperature (LCST) at the same temperature (32?34 °C) than PNIPAM, while the copolymer shows pH dependent UV-vis-NIR absorption similar to PANI. The PNIPAM block suffers a coil to globule transition upon NIR light irradiation (785 nm, 100 mW), as shown by turbidimetry and Atomic Force Microscopy (AFM), due to local heating (more than 9 °C in 12 min) induced by the NIR absorption at the PANI block. Furthermore, the electrical conductivity of PNIPAM-b-PANI thin films is demonstrated (resistivity of 5.3 × 10−4 Ω−1 cm−1), indicating that the PANI block is present in its conductive form.